Exploring Technological Innovations and Approaches in Modern Education - Muh Habibulloh; Munawwaroh; Mutrofin; Muh Ibnu Sholeh; Khoirotul Idawati (Journal of Studies in Academic, Humanities, Research, and Innovation, 2024)
Modern education is currently undergoing a significant transformation with the integration of technology in various aspects of learning. Technological innovations, such as online learning platforms, computer-based applications, and the use of technologies like virtual reality (VR) and augmented reality (AR), have introduced new, more flexible, and interactive approaches to education. This study aims to explore technological innovations and approaches in modern education, as well as their impacts on the learning and teaching process. The research employs a library research method, analyzing various relevant literatures on the application of technology in education. Data was collected through a literature review of journal articles, books, and academic publications discussing this topic. The research findings indicate that technology has brought positive impacts to education, including improvements in access, interactivity, and personalized learning. Additionally, new approaches such as blended learning, gamification, and adaptive learning are increasingly being implemented to meet students' individual needs. However, challenges such as the digital divide and resistance to change remain significant barriers that need to be addressed. This study concludes that, while technology offers various benefits, its implementation requires adequate support from all relevant stakeholders to achieve optimal outcomes.